National Traditions in the Spiritual and Moral Education of Pre-School Children - Tosheva, N. T; Shukurova, M. O'. (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the importance and role of national traditions in children's spiritual and moral education is based on the formation of knowledge, skills and abilities by educating children on the basis of national traditions. In this sense, the article analyzes the purpose of spiritual and moral education in preschool educational institutions.